The Influence of Independent Commissioners, Company Size, and Profitability on Company Value with Loan Interest Rate Moderation - Dwima, Mayang Putri; Ruslim, Herman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to examine the influence of independent commissioners, company size, and profitability on company value with loan interest rates as a moderating variable. This research uses secondary data in the form of financial reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2023 period. By using purposive sampling, a selected sample of 100 was obtained. The testing method used in this research was multiple linear regression analysis of panel data. The research results show that independent commissioners have no effect on company value, company size has a significant positive effect on company value, and profitability has a positive but insignificant effect on company value. This research also found that loan interest rates have a significant negative effect on the relationship between company size and company value as well as the relationship between profitability and company value.